Uji Pemeriksaan Cemaran Total Bakteri, Coliform, Escherichia coli, dan Salmonella sp. pada Ikan Mujair (Oreochromis mossambicus) Hasil Budidaya Keramba Jaring Apung (KJA) di Kawasan Danau Batur, Kintamani, Bangli, Bali - NI Putu Diah Septiani Putri; Retno Kawuri (Metamorfosa: Journal of Biological Sciences, 2024)
Fish is a food that rots easily due to contamination with microorganisms. When consumed, food that has been contaminated with pathogenic bacteria can endanger human health. Tilapia fish (Oreochromis mossambicus) is vertebrate animal that is often cultivated, especially in the Kintamani area. This research was conducted to determine total bacterial contamination, Coliform, E.coli, and Salmonella sp. on tilapia fish cultivated in floating net cages in the Lake Batur area, Kintamani, providing information on the safety and suitability of consuming tilapia fish by food safety standards, as well as providing an overview of differences in bacterial contamination in each location village. The samples were tested using the pour plate and streak plate plating method. Coliform and E. coli bacterial contamination tests were carried out using the Most Probable Number (MPN) method, examining Salmonella sp. carried out on selective Salmonella Shigella Agar (SSA) media. The ALT test results obtained the highest average in tilapia fish samples from Kedisan village, namely 5.9 x 106 CFU/g, the highest average total Coliform was in fish samples from Abang and Batur Tengah villages with values ​​> 1.1 x 104 MPN /g, the highest average E. coli contamination was shown by tilapia fish samples from Abang village, namely >4.64 x 103 MPN/g, and one sample from Batur Tengah village showed positive for Salmonella sp bacteria. Based on these results, all tilapia fish samples exceeded the threshold for ALT, Coliform and E. coli contamination and one sample exceeded the normal limit for Salmonella sp contamination. on food based on BPOM and SNI standards.